Effects of short-term fat adaptation on metabolism and performance of prolonged exercise - Burke, L. M.; Hawley, J. A. (Medicine & Science in Sports & Exercise, 2002)
The concept of manipulating an individuals habitual diet before an exercise bout in an attempt to modify patterns of fuel substrate utilization and enhance subsequent exercise capacity is not new. Modern studies have focused on nutritional and training strategies aimed to optimize endogenous carbohydrate (CHO) stores while simultaneously maximizing the capacity for fat oxidation during continuous, submaximal (60-70% of maximal O uptake [OV0312;O ]) exercise. Such "nutritional periodization" typically encompasses 5-6 d of a high-fat diet (60-70% E) followed by 1-2 d of high-CHO intake (70-80% E; CHO restoration). Despite the brevity of the adaptation period, ingestion of a high-fat diet by endurance-trained athletes results in substantially higher rates of fat oxidation and concomitant muscle glycogen sparing during submaximal exercise compared with an isoenergetic high-CHO diet. Higher rates of fat oxidation during exercise persist even under conditions in which CHO availability is increased, either by having athletes consume a high-CHO meal before exercise and/or ingest glucose solutions during exercise. Yet, despite marked changes in the patterns of fuel utilization that favor fat oxidation, fat-adaptation/CHO restoration strategies do not provide clear benefits to the performance of prolonged endurance exercise.